2010
DOI: 10.1303/aez.2010.239
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of vegetable pesticides on a predatory mirid bug, Pilophorus typicus Distant (Heteroptera: Miridae)

Abstract: The harmful side effects of 11 pesticides, 5 acaricides, and 10 fungicides on nymphs and adults of the predatory mirid bug Pilophorus typicus Distant (Heteroptera: Miridae) were determined by dipping them into solutions of each chemical. Two insect growth regulators (IGRs), buprofezin and cyromazine, were not harmful to nymphal survival of P. typicus on the fifth day. Flufenoxuron, lufenuron, and novaluron (also IGRs) were seriously harmful to nymphal survival of P. typicus on the fifth day. IGRs that were del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
2
6
0
2
Order By: Relevance
“…Furthermore, the synergic toxicity of two routes of exposure (topical and exposure to dried residues) was proved on O. insidiosus , with 100% mortality when exposed to the field rate 40. When topically treated, two other Heteroptera species showed diverging responses: Deraeocoris brevis (Uhler) young instars and adults were resistant to the highest field rate,66 while 100% mortality was observed for Pilophorus typicus Distant nymphs and adults when treated with lower spinosad concentrations (≤96 mg AI L −1 ) 67. The real implication of the effects observed after topical exposures should take into account that spinosyn effect can be magnified by the unrealistic experimental conditions of some studies.…”
Section: Side Effects Of Spinosyns On Non Target Organisms Reported mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the synergic toxicity of two routes of exposure (topical and exposure to dried residues) was proved on O. insidiosus , with 100% mortality when exposed to the field rate 40. When topically treated, two other Heteroptera species showed diverging responses: Deraeocoris brevis (Uhler) young instars and adults were resistant to the highest field rate,66 while 100% mortality was observed for Pilophorus typicus Distant nymphs and adults when treated with lower spinosad concentrations (≤96 mg AI L −1 ) 67. The real implication of the effects observed after topical exposures should take into account that spinosyn effect can be magnified by the unrealistic experimental conditions of some studies.…”
Section: Side Effects Of Spinosyns On Non Target Organisms Reported mentioning
confidence: 99%
“…40 When topically treated, two other Heteroptera species showed diverging responses: Deraeocoris brevis (Uhler) young instars and adults were resistant to the highest field rate, 66 while 100% mortality was observed for Pilophorustypicus Distant nymphs and adults when treated with lower spinosad concentrations (≤96 mg AI L −1 ). 67 The real implication of the effects observed after topical exposures should take into account that spinosyn effect can be magnified by the unrealistic experimental conditions of some studies. The use of organic solvents instead of water as carriers (increasing the pesticide intake inside the arthropod body) and the use of dipping methods instead of spray to apply the pesticide solution can amplify the pesticide toxicity, i.e.…”
Section: Lethal Effect 311 Lethal Effect On Natural Enemiesmentioning
confidence: 99%
“…However, several authors have reported lethal and sublethal effects on non‐target organisms from a range of taxa. These include high mortality in both adults and larvae of the predatory mirid bug Pilophorus typicus , reduced egg hatch in E. balteatus , reduced parasitism rate in M. mediator and the parasitoid beetle Aleochara bilineata and even adverse effects on the infectivity and fecundity of entomopathogenic nematodes as a result of exposure to flonicamid. Jansen et al also reported substantial negative effects on the survival and reproduction of Aphidius rhopalosiphi and Adalia bipunctata , but these effects were not observed in insects exposed to the insecticide on sprayed plants rather than a glass surface.…”
Section: Introductionmentioning
confidence: 99%
“…Arnó & Gabarra (2011), spinosad'ın 25 ml/100 litre dozunun N. tenuis ve M. pygmaeus 3. ve 4. dönem nimfleri ile erginlerine zararsız olduğundan bahsederken Tedeschi et al (2001), ise spinosad'ın 20 ml/100 litre dozunun M. pygmaeus 1. ve 2. dönem nimflerine yüksek düzeyde zararlı olduğunu belirtmektedirler. Nakahira et al (2010), ise başka bir Mirid olan Pilophorus typicus Distant (Heteroptera: Miridae)'a spinosad'ın 25 ml/100 lt dozunun %100 oranında etkili olduğundan bahsetmektedir. Van de Veire & Tirry (2003), spinosad'ın 20 ml/100 litre dozunun M. caliginosus'un 2. ve 3. dönem nimflerine 24 saat sonra %12, 72 saat sonunda ise %40 civarında bir ölüme neden olduğu bildirmişlerdir.…”
Section: Araştırma Sonuçları Ve Tartışma İlaçların Nesidiocoris Tenuiunclassified